Trimline Mapping from Multispectral Landsat ETM+ Imagery - Csatho, Bea; Van Der Veen, Cornelis; Tremper, Catherine (Géographie physique et Quaternaire, 2005)
AbstractMultispectral Landsat ETM+ imagery is used to study the ice-marginal region in the vicinity of Jakobshavn Isfjord, west Greenland. In particular, the trimline indicating margin retreat since the maximum stand attained during the Little Ice Age maximum is reconstructed, and compared with earlier maps based on aerial photogrammetry and ground surveys. Applying supervised classification, fourteen different surface types were identified, ranging from snow and ice, debris-covered ice and water with differing turbidities, to different types of vegetative landcover. After similar classes were merged into five, distinctively different classes, a digitized geomorphologic map was used to assess the accuracy of the classification. The positional accuracy of the trimline was checked by using results from a GPS survey along northern slope of the Jakobshavn fjord. By merging three spectral bands with the panchromatic band, a pan-sharpened image with a spatial resolution of 15 m is obtained that clearly shows morphological features on the ice surface, as well as increased resolution of glacial geomorphology.